1999
DOI: 10.1111/j.1346-8138.1999.tb03473.x
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Role of Candida albicans Antigen in Atopic Dermatitis

Abstract: An immediate hypersensitivity reaction to Candida albicans (C. albicans) antigen has been observed in patients with atopic dermatitis. Recent data from a comparative study of the immune response to C. albicans antigen in patients with atopic dermatitis and non-atopics suggest a shift form type 1 helper T cells to type 2 helper T cells in the immune response to C. albicans antigen in atopic dermatitis. To delineate the role of C. albicans in the pathogenesis in atopic dermatitis, we evaluated skin reaction of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
0
21
0
6
Order By: Relevance
“…The yeasts reputed to be the most allergenic are C. albicans, Saccaromyces cerevisiae and Saccaromyces minor (484) and Pityrosporum (485). Immunoglobulin E-mediated sensitization to yeasts has been shown, particularly in atopic dermatitis (485)(486)(487)(488). Most yeasts present cross-reactive antigens (489).…”
Section: Other Mitesmentioning
confidence: 99%
“…The yeasts reputed to be the most allergenic are C. albicans, Saccaromyces cerevisiae and Saccaromyces minor (484) and Pityrosporum (485). Immunoglobulin E-mediated sensitization to yeasts has been shown, particularly in atopic dermatitis (485)(486)(487)(488). Most yeasts present cross-reactive antigens (489).…”
Section: Other Mitesmentioning
confidence: 99%
“…mit Ketoconazol) untersucht [196,197]. Unter der Therapie besserte sich der klinische Aktivitätsscore und die Konzentration an IgEAntikörpern sank.…”
Section: Bessern Sich Candidaassoziierte Beschwerden Unter Antimykotiunclassified
“…However, no significant differences between AD patients and controls were seen. Morita et al found that the total IgE level was significantly higher in patients with AD (37 patients) than in both patients with allergic rhinitis (23 patients) and healthy controls (42 subjects) (106). C. albicans-specific IgE was found in 85% of AD patients compared to only 9% of patients with allergic rhinitis and 5% of healthy controls.…”
Section: Atopic Dermatitis and The Candida Yeastsmentioning
confidence: 99%